Pulmonary vein isolation by pulsed-field ablation induces smaller neurocardiac damage than cryoballoon ablation. (19th May 2022) - Lemoine, M; Mencke, C; Schleberger, R; Muenkler, P; Wieboldt, H; Scherschel, C; Dinshaw, L; Reissmann, B; Ouyang, F; Fabritz, L; Zeller, T; Meyer, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): FARAPULSE, Inc. Introduction: Thermal energy sources damage the entire atrial tissue during pulmonary vein isolation (PVI) including cardiac nerves and ganglia. This induces a postinterventional increase in heart rate. Pulsed-field ablation (PFA), a new non-thermal energy source for PVI, primarily damages cardiomyocytes by electroporation. Whether use of PFA reduces damage to cardiac nerves and ganglia and influences postinterventional increase of heart rate is not known. Purpose: We compared the acute effects of PFA with a pentaspline catheter and cryoballoon ablation (CBA) on secretion of circulating biomolecules reflecting cardiomyocyte and neuronal injury and postinterventional increase in heart rate to estimate damage to the cardiac autonomic nervous system and autonomic dysfunction after PVI. Methods: Blood samples were taken before and after PVI in consecutive patients undergoing PFA and CBA. All patients participated in the TRUST registry. Serum concentrations of high-sensitive Troponin I (hsTropI, Immunoassay) and S100b (ELISA), a surrogate marker for neuronal injury, were quantified in blood samples taken prior to PVI and directly after PVI. Pre- and postinterventional heart rates were measured in ECGs and Holter-ECGs. Results: Fifty-six patients underwent PVI, either by PFA (n=28, age 63 [54; 75] y, 64% males, 57% persistent AF) or CBA (n=28, age 71 [62; 78] y, 61% males, 54% persistent AF). All 112 blood samples were analyzable. Acute success of PVI was 100% in both groups without major complications, especially, no TIA and no stroke. After CBA, one patient suffered from phrenic palsy, which reversed after 3 months. HsTropI increased 3.3-fold more after PFA compared to CBA (625±138 vs. 185±42 pg/ml; p=0.004) suggesting more damage to cardiomyocytyes. S100b increased 2.9-fold less after PFA compared to CBA (21.1±3.7 vs. 61.2±8.1 pg/ml; p<0.001). The ratio of ∆S100b/∆hsTropI was five-fold smaller after PFA compared to CBA (0.19±0.1 vs. 0.98±0.3; p=0.007), suggesting a lower neurocardiac injury in comparison to lesion size. Concomitantly, increase in heart rate at the postinterventional day was smaller in PFA (-0.2±3.0 bpm; n=45) than in CBA (+6.1±2.7 bpm, n=15; p=0.024). Conclusion: This study in patients validates the experimental concept that PFA-based AF ablation leads to more specific damage to cardiomyocytes than to cardiac nerves and ganglia, reflected by lower S100B concentrations and no post-interventional heart rate increase compared to CBA.